1991
DOI: 10.5980/jpnjurol1989.82.1972
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Intraoperative Autotransfusion During Urological Operation

Abstract: The value of autotransfusion is widely recognized in the surgical community and may be of increasing importance in prevention of acquired immunodeficiency syndrome and hepatitis. The concern of possible contamination of the blood with urine, bacteria in urine or viable tumor cells has limited the wide use of intraoperative autotransfusion (IAT) in urological operation. There have been no experimental reports about protection of the blood from such contamination. To investigate separation of the blood from a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The use of IAT during RP has remained controversial because of conflicting evidence on the risk of haematogenous tumour dissemination. Several in vitro studies suggested that tumour cells are not cleared during Cell Saver blood processing [6,10,11], but retrospective studies showed no greater risk of prostate cancer recurrence when IAT was used [2,3]. Other specialities have also reported no greater rate of tumour recurrence or metastasis when IAT is used during oncological surgery [12–14].…”
Section: Discussionmentioning
confidence: 99%
“…The use of IAT during RP has remained controversial because of conflicting evidence on the risk of haematogenous tumour dissemination. Several in vitro studies suggested that tumour cells are not cleared during Cell Saver blood processing [6,10,11], but retrospective studies showed no greater risk of prostate cancer recurrence when IAT was used [2,3]. Other specialities have also reported no greater rate of tumour recurrence or metastasis when IAT is used during oncological surgery [12–14].…”
Section: Discussionmentioning
confidence: 99%
“…Washing has been shown to eliminate or significantly reduce chemical and physical contaminants. In terms of bodily fluids, one study shows complete removal of urine from a 50% blood : urine mix by washing 73 . Even so, there have not been any reports of adverse clinical events due to transfusion of unwashed salvaged blood that has become admixed with urine 43 .…”
Section: Washingmentioning
confidence: 99%
“…The concern is inducing metastatic spread of the cancer that is being operated on. It has been shown that salvaged blood from cancer surgery does contain tumor cells, and that washing alone is not enough to remove them 73,84,85 . To reduce the number of potentially malignant cells, leukocyte depletion filters have been advocated and have been shown to reduce the number of tumor cells 85–87 .…”
Section: Filteringmentioning
confidence: 99%
“…Park et al . (1991 , 1997) investigated the efficacy of the ICS washing step for removing bacteria and urine from salvaged blood.…”
Section: Infected Fieldsmentioning
confidence: 99%
“…(1991 , 1997) investigated the efficacy of the ICS washing step for removing bacteria and urine from salvaged blood. In the first series of three experiments ( Park et al ., 1991 ), 200 mL of blood was mixed with 200 mL of urine and then processed on a Haemonetics Cell Saver, and the cell concentrate (CC) was biochemically analysed. Next 200 mL of blood was mixed with 200 mL of urine, which had been contaminated with 10 7 organisms mL −1 of each of four bacterial strains and the resulting CC was cultured.…”
Section: Infected Fieldsmentioning
confidence: 99%